Geomorphology and late Holocene accretion history of Adele Reef: a northwest Australian mid-shelf platform reef - Solihuddin, T.; Bufarale, G.; Blakeway, David; O'Leary, M. (2016)
The mid-shelf reefs of the Kimberley Bioregion are one of Australia’s more remote tropical reef provinces and such have received little attention from reef researchers. This study describes the geomorphology and late Holocene accretion history of Adele Reef, a mid-shelf platform reef, through remote sensing of contemporary reef habitats, shallow seismic profiling, shallow percussion coring and radiocarbon dating. Seismic profiling indicates that the Holocene reef sequence is 25 to 35 m thick and overlies at least three earlier stages of reef build-up, interpreted as deposited during marine isotope stages 5, 7 and 9 respectively. The cored shallow subsurface facies of Adele Reef are predominantly detrital, comprising small coral colonies and fragments in a sandy matrix. Reef cores indicate a ‘catch-up’ growth pattern, with the reef flat being approximately 5–10 m deep when sea level stabilised at its present elevation 6,500 years BP. The reef flat is rimmed by a broad low-relief reef crest only 10–20 cm high, characterised by anastomosing ridges of rhodoliths and coralliths. The depth of the Holocene/last interglacial contact (25–30 m) suggests a subsidence rate of 0.2 mm/year for Adele Reef since the last interglacial. This value, incorporated with subsidence rates from Cockatoo Island (inshore) and Scott Reefs (offshore), provides the first quantitative estimate of hinge subsidence for the Kimberley coast and adjacent shelf, with progressively greater subsidence across the shelf.